Sari Beach Ecotourism Development Strategy, Pakis Village, Banyuwangi District, Banyuwangi Regency Kabupaten - Mega Yuniartik; Agustina Tri Kusuma Dewi; Magdalena Putri Nugrahani (Journal of Aquaculture Science, 2021)
Sariah Beach is one of the ecotourism potentials located in the village of Pakis, Banyuwangi with the characteristics of black sand, true mangrove vegetation, and associations, pine trees. This study aims to determine the development of community-based ecotourism and natural resources. The research method uses descriptive quantitative Focus Group Discussion (FGD), to determine IFAS and EFAS. Data analysis using SWOT analysis. The results showed alternative ecotourism development strategies which included increasing knowledge and technology in resource-based communities, improving supporting facilities and infrastructure, managing mangrove-based ecotourism, avifauna diversity, and maintaining turtle conservation. Furthermore, the integration of interests involving stakeholders at Sari beach.Keywords: ecotourism, mangrove, development, Sariah Beach